Approche de l’efficacité de la gouvernance par le biais de la cohésion des audits interne et externe conformément à la norme algérienne d’audit NAA 610. – Etude analytique - - laieb, fouzia; amara, meriem (Journal of Research in Finance and Accounting, 2026)
This research paper aims to study the role and importance of the integration between internal audit and external audit and its effects on the dimensions of governance, and in order to achieve the research objectives, a questionnaire was distributed to a random sample of academics. Audit specialty and professional Accounts Governor and auditors, in order to process the data obtained by the questionnaire we used the SPSS software version 21. The results of the study confirms the relationship between the integration of internal and external audit and that this relationship has an effect on the activation of the dimensions of governance. The effect of the accreditation index, the confidence index on the work of the internal auditor and the added value accumulated from the use of its results gives an effect on the integration between internal audit and external audit and the extension of the influence of this integration in the activation of the prudential, strategic, disclosure and ethics dimension of governance, on the other hand The effect of the integration between internal and external audit on the operational dimension of corporate governance. has not been proven.